THE ROLE OF INDIVIDUAL, MANAGER, AND EXECUTIVE IN EMPLOYEE ENGAGEMENT: CASE OF INDONESIA CENTER FOR SUSTAINABLE DEVELOPMENT BANDUNG - Abdillah, Faizal
Globalization is forcing companies to create a global strategy to gain competitive advantages by optimizing all of their resources including human resources. The purpose of this research is to identify roles that influence level of employee engagement in a consultant company named Indonesia Center for Sustainable Development Bandung. This research only focuses on strategies of ICSDB in building employee engagement and does not discuss the measurement of employee engagement level. It also evaluates the existing theory of employee engagement that can be useful to enrich the understanding contextually. Based on several studies on employee engagement has been done, there are still few studies conducted in a consultant company. Therefore, this study seeks to use a newly established consultant company as the research object that is still rarely done by other researchers. Participant observation and indepth interview are two main tools used in ethnography method as the data collection method in this study. The domain analysis is used as the data analysis method to interpret the influential roles in employee engagement based on particular theory. Each individuals, managers, and executive of ICSDB have their respective roles in the level of employee engagement. This studies concludes that managers have more dominant role in ch is a specific and unique tool used by the ICSDB managers to increase the engagement level. In addition, - the significant factor to improve employee engagement level through emotional relationship between ICSDB as the server and their developed community as the client. This study suggests the ICSDB team members to strengthen their sense of ownership to increase the engagement level towards the ICSDB. In addition, ICSDB need to build some small teams if they already have a lot of employees to repeat their small team strategy that have been successful to create engagement.